Initial predictors of skin thickness progression in patients with diffuse cutaneous systemic sclerosis: Results from a multicentre prospective cohort in Japan. Issue 2 (4th March 2021) - Kuwana, Masataka; Hasegawa, Minoru; Fukue, Ryosuke; Shirai, Yuichiro; Ishikawa, Osamu; Endo, Hirahito; Ogawa, Fumihide; Goto, Daisuke; Kawaguchi, Yasushi; Sato, Shinichi; Ihn, Hironobu; Takehara, Kazuhiko
Abstract: Objective: To identify initial parameters that predict worsening of skin thickening in patients with diffuse cutaneous systemic sclerosis (dcSSc) using a multicentre, prospective, observational cohort in Japan. Methods: A total of 171 patients with dcSSc were selected from a prospective cohort database based on the following criteria: dcSSc, modified Rodnan total skin thickness score (mRSS) ≥7, disease duration <60 months, and valid mRSS data at one year. Worsening of skin thickness was defined as an increase in mRSS ≥3 points and an increase ≥25% from baseline to one year. Initial demographic and clinical parameters useful for predicting the progression of skin thickness were identified using univariate and multivariable analysis, and prediction models of skin thickening progression were built based on combinations of independent predictive parameters. Results: Only 23 patients (13.5%) experienced worsening mRSSs at one year. Short disease duration, low mRSS, absence of nailfold bleeding, arthritis, and a high erythrocyte sedimentation rate at diagnosis were identified as predictors of subsequent worsening of the mRSS even after adjusting for the treatment. Assessment of the best predictive model revealed that patients with a disease duration ≤12 months and mRSS ≤19 had a risk of mRSS worsening within one year, with a sensitivity of 73.9% and specificity of 81.1%. Conclusion: Identification of predictors of subsequent worsening of skin thickness in dcSSc patients is useful for identifying patients who require intensive treatment with potential disease-modifying agents and for improving clinical trial design by characterizing eligible progressors in the Japanese population.